If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1x = 4x + 21 Reorder the terms: 6 + -1x = 21 + 4x Solving 6 + -1x = 21 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -1x + -4x = 21 + 4x + -4x Combine like terms: -1x + -4x = -5x 6 + -5x = 21 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -5x = 21 + 0 6 + -5x = 21 Add '-6' to each side of the equation. 6 + -6 + -5x = 21 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 21 + -6 -5x = 21 + -6 Combine like terms: 21 + -6 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| -7=7.37802(x)+(-4.9)(x^2) | | 5t-2=34-t | | 125+10x=230+2x | | (2q-3)q=27 | | 12y+6=12y+7 | | 5x+28=x | | 42+3x(6+1)+4=24 | | 9x+30=27 | | 20-4(p+1.25)=5+p | | 0=-16x^2+16x+320 | | (2w+7)w=99 | | 0.3a+.7=.5a-.1 | | -8(3p+2)+2(-5+7p)=-66 | | 2(x-1)+3x=3(-2+x) | | 1.5*1= | | (2x^2+8x+1)= | | f(x)=15x+10 | | (2w+11)w=63 | | (8-z)(5z-9)=0 | | 5(1-8k)+4(3k+7)=61 | | 2w+11=63 | | -3-2x+5=5+x-2x | | 8+8(-2g+4)=4(-4g+10) | | 7-5(-7b-1)=-8(3-4b) | | 5+x(53)+8=52 | | -3x^2-6x-21=0 | | 13x+3=23+3x | | 7m(m-1)=3(1-m) | | g(b+8)=8x+5 | | (2w-5)w=33 | | X-3-3x=-3(1+x) | | (3x^2+22x-16)= |